2020
DOI: 10.21873/invivo.11803
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Comparative Proteomics Reveals Candidate Biomarkers for the Early Prediction of Gestational Diabetes Mellitus: A Preliminary Study

Abstract: Aim: To identify differentially expressed proteins (DEPs) in 1 st trimester maternal plasma between pregnant women at risk for gestational diabetes mellitus (GDM) and uncomplicated controls. Materials and Methods: Firsttrimester plasma from five women who developed GDM and five from non-diabetic ones were analyzed using isobaric tag for relative and absolute quantitation -labeled proteomics. Enzyme-linked immunosorbent assay was further applied in an independent cohort of 25 GDM cases and 25 controls for verif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Several of the proteins identified in our study have been previously reported by other groups at early GDM biomarkers screening including sex hormone‐binding globulin (SHBG), C‐reactive protein (CRP), serum amyloid P‐component, and fibrinogen alpha chain reported as candidate biomarkers 28,34,35 . Recently, Mavreli et al 18 using proteomic analyses identified overexpression of prenylcysteine oxidase 1 (PCYOX1), beta‐ala‐his dipeptidase (CNDP1), extracellular matrix protein 1 (ECM1), basement membrane‐specific heparan sulfate proteoglycan core protein (HSPG2), and thrombospondin 4 (TSP‐4) in the 1st‐trimester maternal plasma of women who were subsequently diagnosed with GDM followed by confirmatory ELISA.…”
Section: Discussionsupporting
confidence: 69%
“…Several of the proteins identified in our study have been previously reported by other groups at early GDM biomarkers screening including sex hormone‐binding globulin (SHBG), C‐reactive protein (CRP), serum amyloid P‐component, and fibrinogen alpha chain reported as candidate biomarkers 28,34,35 . Recently, Mavreli et al 18 using proteomic analyses identified overexpression of prenylcysteine oxidase 1 (PCYOX1), beta‐ala‐his dipeptidase (CNDP1), extracellular matrix protein 1 (ECM1), basement membrane‐specific heparan sulfate proteoglycan core protein (HSPG2), and thrombospondin 4 (TSP‐4) in the 1st‐trimester maternal plasma of women who were subsequently diagnosed with GDM followed by confirmatory ELISA.…”
Section: Discussionsupporting
confidence: 69%
“…Plasma or serum components can further be extracted from blood to remove cell parts or platelets. Among the ten studies using peripheral blood, five studies used plasma specimens (Figure 1(b)) [27,32,39,44,47], and the remaining studies used serum samples. Moreover, there is also a growing trend for seeking noninvasive testing strategies nowadays.…”
Section: Summary Of Proteomic Studies Of Gdmmentioning
confidence: 99%
“…In addition to clinical validation or functional verification, eight studies also performed expression verification experiments using immunodepletion, western blot, immunohistochemistry, real-time polymerase chain reaction, or bioinformatics database (the Human Protein Atlas) [55] to verify the existence, localization, and change trend of DE proteins. Table 1, five studies evaluated the diagnostic efficiency of a selected list of significantly changed proteins [31,37,38,42,47]. The concentrations of target proteins were measured by the ELISA or MRM method in serum, plasma, or urine samples.…”
Section: General Experimental Workflowmentioning
confidence: 99%
See 2 more Smart Citations